To What Degree Does Limb Spasticity Affect Motor Performance in Para-Footballers With Cerebral Palsy? - Roldan, Alba; Henríquez, Matías; Iturricastillo, Aitor; Castillo, Daniel; Yanci, Javier; Reina, Raul (Frontiers in Physiology, 2022)
Spasticity is considered a contributor to hypertonia, frequently presented in people with cerebral palsy (CP), affecting muscle function and motor activities. In CP football, the classification system determines that this impairment is eligible for competitive para-sports due to the impact on activity limitation and sports performance. However, the relationship between this feature (i.e., spastic hypertonia) and performance determinants has not been explored yet. This study aimed to assess the association of clinical spasticity measurements with the performance of sport-specific tests used for classification purposes. Sixty-nine international footballers with CP voluntarily participated in this study. The Australian Spasticity Assessment Scale was used to measure spasticity in lower limbs muscle groups and activity limitation tests were conducted considering dynamic balance, coordination, vertical and horizontal jumps, acceleration, and change of direction ability. Low-to-moderate negative significant associations were found between the hip spasticity and measures of dynamic balance and dominant unipedal horizontal jump capacity. Additionally, moderate associations were reported between the knee spasticity and the non-dominant unipedal horizontal jump capacity and the change of direction actions with the ball. The ankle spasticity score reported small to moderate associations with the change of direction assessment without the ball and bipedal and dominant unipedal horizontal jump capability. Finally, the total spasticity score only presented a significant association with horizontal jump performance. This is a novel study that provides evidence of the associations between an eligible neural impairment and relevant specific measures of activity limitation tests. These results suggest that the amount of spasticity according to each evaluated joint muscle group of the lower limbs presents a low-to-moderate significant relationship with determined measures of dynamic balance, coordination, horizontal jump, acceleration, and change of direction ability with and without the ball in international-level CP footballers. Further studies are necessary to elucidate the real contribution of neural and non-neural impairments related to hypertonia on fundamental sport-specific motor skills of para-footballers with CP.